Working capital management and its effect on profitability: empirical evidence from Malaysian capital market / Rahimah Mohamed Yunos ... [et al.] - Mohamed Yunos, Rahimah; Abdol Ghapar, Farha; Ahmad, Syahrul Ahmar; Sungip, Noraisah (UiTM Cawangan Johor, 2018)
This study examines the effect of working capital management on profitability among 803 companies listed on Bursa Malaysia. The data collected from DataStream for the year 2010 to 2014 was analyzed using panel data analysis. It was found that number of sales inventory days and number of account receivable days determine profitability of Malaysian public listed companies. Additionally, the debt to equity ratio, current ratio and firm size also has significant effects on the firm's profitability.